The Business of Healthcare and the Economics of Healthcare: Shall Ever the Twain Meet?. Issue 1 (2nd January 2018) - Pauly, Mark V.
Abstract: This note discusses the differing viewpoints of economic analysis and business leader perceptions of the causes and possible remedies for rising medical care spending that has persisted for many years. The economic approach does not necessarily view spending growth as harmful if the additional beneficial but costly new technology it has historically purchased is worth the cost, and if the additional cost is perceived by decision makers to be ultimately borne by workers in lower wages, not by owners as higher compensation costs or lower capital returns. Possible accommodations to our inability to eliminate (or even define) "waste" in the medical care sector are discussed.